Subjective Performance Evaluation and Gender Discrimination - Maas, Victor S.; Torres-González, Raquel (2011)
Gender discrimination continues to be a problem in organizations. It is therefore important that organizations use performance evaluation methods that ensure equal opportunities for men and women. This article reports the results of an experiment to investigate whether and, if so, how the gender of the rater and that of the ratee moderate the relationship between the level of subjectivity in performance appraisals and organizational attractiveness. Participants in the experiment were 313 undergraduate students. We predicted, and indeed established, that as the probability increases that employee performance is evaluated by a female manager, women expect more positive outcomes of subjective, but not objective evaluation processes. Our data did not support our expectation that as the probability of being evaluated by a female manager increases, men expect less positive outcomes of subjective evaluation processes. The findings of this study contribute to our understanding of why women are over-represented in jobs with objective formula-based reward systems, such as piece-rate systems. They are also of interest to organizations that are looking for more ethical human resource management practices.
Keywords: sex bias; Gender; Subjectivity; Performance Appraisal